Adverse childhood experiences and chronic pain in adults aged 86: findings from the Lothian Birth Cohort 1936 - Senaratne, Dhaneesha N. S.; Singleton, Sam; Timmins, Kate; Spiteri, Jeanette; Redmond, Paul; Taylor, Adele; Corley, Janie; Page, Danielle; Rennie, Janine; Wang, Huan; Verriotis, Madeleine; Walker, Suellen M.; et al. (Frontiers in Aging, 2025)
BackgroundChronic pain, a major cause of disability, is prevalent in older people. Exposure to multiple adverse childhood experiences (ACEs) is associated with increased levels of chronic pain in later life. However, this association has not been investigated in people aged older than 80 years. Therefore, the primary objective of this study was to explore the relationship between ACEs and chronic pain in people with a mean age of 86 years, participants of the Lothian Birth Cohort 1936.MethodsA survey co-developed by researchers, clinicians and people with lived experience (PWLE) that assessed chronic pain and ACEs was completed by 229 participants (response rate 67%). Associations between ACE exposure and chronic pain were investigated using multinomial logistic regression.ResultsResults showed that 58% reported chronic pain, with a higher prevalence in females. Furthermore, 69% of participants with chronic pain reported moderate or severe pain interference and 82% reported at least 1 ACE, with 25% indicating exposure to ≥4 ACEs. The most frequently reported exposure was community violence (48%). Males were more likely to report any ACE, physical neglect, bullying, and community violence. No significant association was found between ACEs and chronic pain status, severity, or interference in this cohort.DiscussionThis study, the first to adapt ACE and chronic pain questionnaires with input from PWLE, suggests that the relationship between ACEs and chronic pain may be less relevant in people in their eighties compared to younger populations. These findings have implications for trauma-informed care and pharmacological treatment in older adults.